More on Non-White Poverty and Economic Growth - Hoover, Gary A; Collins, Sondra R; Yaya, Mehmet E. (Journal of Income Distribution®, 2011)
We use Seemingly Unrelated Regressions (SUR), to explore the impact of three different measures of economic activity -- growth in Gross Domestic Product (GDP), unemployment, and manufacturing employment -- on poverty among whites, blacks and Hispanics in the United States. This analysis is unique in that we further disaggregate the data, by looking at the impact of growth across racial/ethnic groups in four census regions. We find that the impacts of the various measures of economic activity vary greatly by the group and the region. In particular, Hispanic poverty tends to be strongly related to changes in the unemployment rate, while white poverty tends to be strongly related to changes in manufacturing.